Balancing bicycle by steering control - Mello, Gamage Don Anton Sachintha; Manukid Parnichkun; Bohez, Erik L.J.; Lin, Than (Pathum Thani, Thailand : Asian Institute of Technology, 2014)
A recumbent is a very unstable bicycle yet known as for its efficiency and ride comfort. Riding a bike on this particular type requires a skill more than a more conventional bike layout that most of us are used to. This report contains of a development of a small scale recumbent style bicycle that is been developed to balance by its own during the forward motion. Active steering control that is been controlled by the classical PID algorithm is used as the balancing mechanism.
A capstone project report submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Engineering in Mechatronics Engineering, School of Engineering and Technology
Capstone Project (B. Sc.) - Asian Institute of Technology, 2014
Keywords: Bicycles -- Dynamics